Grußformeln als Medium der Polemik in Augustins Briefen - Nunn, Christopher Alexander (Zeitschrift für antikes Christentum, 2018)
The analysis of salutations is often disregarded because they are said to be later additions of copyists or at least conventional phrases without any content. But the correspondence of Augustine suggests that the bishop himself composed the recorded salutations and that he even added a subtext in many cases. The survey sheds light on elements, development, and different functions of salutations in order to show that, at least in Augustine’s correspondence, an analysis of the salutations is a valuable resource to describe not only the social differences between sender and recipient, but also the atmosphere, the reason for writing, and the correspondents’ relationship to each other.